Mutation analysis of TP53 in colorectal cancer, Peshawar, Khyber Pakhtunkhwa, Pakistan. - Mian Adnan Kakakhel; Ihsan Ali; Aamna Fayyaz; Zahid Anwar; Irfan Saif; Ikram Khan; Muhammad Jahangir (National Scientific Medical Center, 2021)
Aim: Colorectal cancer is a kind of solid tumor and third most common of cancer which leads to death. It is a heterogeneous disease characterized by genetic and epigenetic aberrations. The present study was aimed to reveal the mutation at TP53 in Peshawar Pakistan. Material and methods: For this purpose, a total of 50 blood samples in EDTA tubes was collected from Peshawar with complete information of patients using questionnaire. The polymerase chain reaction was performed. Results: The results of the present study have revealed that the ratio of colorectal cancer in males is higher 62% than females (38%). Histopathological results have indicated that moderately differentiated adenocarcinoma is 25 (50%) followed by poorly differentiated adenocarcinoma 15 (30%), Well-differentiated adenocarcinoma 8 (16%), and Metastatic adenocarcinoma 2 (4%) in 50 colorectal cancer patients. The nucleotide sequence of the human TP53 gene of colorectal cancer patients was aligned with the human wild-type TP53 database sequence with NC_191170 (NCBI) using CLUSTALW. After BLASTING, the mutation was found in exon 5 and exon 7 of TP53, while no mutation was found in exon 8 of TP53. That patient in which point mutation was found in exon 5 and 7 respectively showed less survival as compared to that of colorectal cancer patients having no point mutation in the TP53 gene. Conclusion: The present study concluded that point mutations were found in exons 5&7 of the TP53 gene and patients having TP53 gene mutations shown less survival rate compared to colorectal cancer patients having no mutations.